REALITY THEORY APPROACH IN STRESS MANAGEMENT IN DRUG CASE INMATES IN CLASS II A BANYUWANGI PRISON - Syarruch Barucha, Achmad Azza; Hafifah, Nur (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2024)
Stress management in the Correctional Institution (Lapas) environment is a major challenge, especially for drug case inmates who face psychological pressure due to loss of freedom, separation from family, and anxiety related to social relationships. This study aims to explore the application of Reality Theory with the WDEP (Wants, Doing, Evaluation, Planning) technique in helping inmates manage their stress and anxiety. This study uses a descriptive qualitative approach with the main subject being an inmate at Banyuwangi Class IIA Prison who experiences deep anxiety related to his relationship with his child. The results of the study showed that the WDEP technique was effective in helping subjects identify their deepest desires, evaluate actions that have been taken so far, and design concrete steps to achieve better life goals. The data in this study reported a significant decrease in anxiety levels after several counseling sessions, improved sleep quality, and better involvement in spiritual activities such as reading the Qur'an and dhikr. This technique also helped subjects prepare themselves to face difficult conversations with their children honestly and openly. This study concludes that the application of Reality Theory with the WDEP technique is not only effective in reducing stress and anxiety, but also has a positive impact on the psychological well-being and readiness for social reintegration of inmates. This approach is recommended to be integrated into the coaching program in prisons to support a more holistic rehabilitation process